Students Mental Health and Learning Performance: The Moderating Impact of College Games - Iis Marwan; Nia Rohayati (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study aims to examine the relationship between the mental health (MH) of Indonesian students and their academic performance, taking into account the significant significance of college sports. The Indonesian government's educational strategies have neglected the educational sector of sports. However, European nations are incorporating athletics into education to enhance student achievement. The participants in this study are students from several Indonesian public colleges. The study evaluated whether indoor and outdoor games for the development of mental health have an excellent effect on student performance. This research has supported a novel learning performance model that significantly contributes to knowledge. This research's theoretical development is essential for comprehending the connection between students' mental health and academic success. This study offered the Indonesian government recommendations for reforming the educational policy and incorporating the vital function of sports into the educational system. Finally, the research has outlined the directions for future investigations by other academics that will add to the body of knowledge.